Altersdemenz und lokale Fürsorge: Ein deutsch-japanischer Vergleich - Lewerich, Ludgera; Shimada, Shingo; Spoden, Celia (transcript, 2018)
How do societies deal with the challenge of senile dementia? By means of a culturally comparative analysis, this volume presents two different approaches, and shows new ways of caring for people with dementia.